The Relationship Between Mother's Knowledge and Husband's Support with The Accuracy of Pentavalent Booster Immunization in Children Aged 18 Months To ≤ 24 Months in Cibadak Village Rawamerta Karawang in 2022 - Sri Wahyuni, Yuni; Putri Rahmadhena, Melisa (Jurnal EduHealth, 2022)
Pentavalent booster immunization is given to prevent diphtheria, pertussis, tetanus, hepatitis B, pneumonia and meningitis caused by Haemophilus influenza type b (Hib). The high incidence of DPT in Indonesia has made the government try to carry out Advanced DPT immunization (Booster), because Advanced DPT immunization (Booster) is important in an effort to maintain high levels of immunity so that it can provide optimal protection. This study aims to determine the relationship between mother's knowledge and husband's support with the accuracy of pentavalen booster immunization in children aged 18 months to ≤ 24 months in Cibadak Village Rawamerta Karawang in 2022. Methods: This type of analytical research was designed with a cross sectional design. The population of this study were all mothers who had children aged 24 months to 48 months as many as 106 people. The sample used was 52 people from the population. The data used were primary data and secondary data, using questionnaires, and analyzed using the chi-square test. Results: The results showed that there was a relationship between mother's knowledge and husband's support with accuracy administering pentavalent booster immunization to children 18 months to ≤ 24 months in Cibadak Village, Rawamerta sub-district, Karawang Regency, West Java in 2022. Conclusion : It is hoped that posyandu cadres in Cibadak Village can invite mothers who have children under five to bring their children to posyandu for complete basic immunization to pentavalent booster immunization to improve the health status of toddlers.